Glycosaminoglycan concentration in cancer tissue - Bar, Piotr; Galiniak, Sabina; Bartusik-Aebisher, Dorota; Filip, Rafał; Aebisher, David (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
Introduction. Glycosaminoglycans (GAGs) play a widespread role in tissue modelling. GAG polymers may affect several receptor pathways in parallel. Aim. To present difference in concentration of GAG in healthy and cancer tissues. Material and methods. The literature search was performed nd reviewed using selected keywords. Results. We revieved the methods of detection various types of glycans measured by Magnetic Resonance Imaging. Conclusion. MRI methodology provides an efficient tool forstudy of cellular composition. The use T1 aof T2 measurements to study cancer tissue is a promising assay.
Dorota Bartusik-Aebisher acknowledges support from the National Center of Science NCN (New drug delivery systems-MRI study, Grant OPUS-13 number 2017/25/B/ST4/02481).
Keywords: fixed charge density; glycosaminoglycan; magnetic resonance imaging